UNIT 7.15 Overview of Experimental Models of the Blood‐Brain Barrier in CNS Drug Discovery. Issue 1 (8th October 2013) - Palmer, Alan M.; Alavijeh, Mohammad S.
Abstract: The blood‐brain barrier (BBB) is a physical and metabolic entity that isolates the brain from the systemic circulation. The barrier consists of tight junctions between endothelial cells that contain egress transporters and catabolic enzymes. To cross the BBB, a drug must possess the appropriate physicochemical properties to achieve a sufficient time‐concentration profile in brain interstitial fluid (ISF). In this overview, we review techniques to measure BBB permeation, which is evidenced by the free concentration of compound in brain ISF over time. We consider a number of measurement techniques, including in vivo microdialysis and brain receptor occupancy following perfusion. Consideration is also given to the endothelial and nonendothelial cell systems used to assess both the BBB permeation of a test compound and its interactions with egress transporters, and computer models employed for predicting passive permeation and the probability of interactions with BBB transporters. Curr. Protoc. Pharmacol . 62:7.15.1‐7.15.30. © 2013 by John Wiley & Sons, Inc.